OPTIMALISASI PEMANFAATAN LIMBAH DAPUR SEBAGAI PUPUK ORGANIK CAIR (POC) UNTUK LINGKUNGAN PERTANIAN DI DESA MUJUR KECEMATAN PRAYA TIMUR KABUPATEN LOMBOK TENGAH - Aprianti, Nurhalisa; Supeno, Bambang (Jurnal Wicara, 2024)
Liquid organic fertilizer is a solution derived from the decomposition of organic materials such as vegetable, fruit, or household waste. The research aims to investigate the effect of organic waste mixture on liquid fertilizer that meets Indonesian National Standard (SNI). The method used is a direct experiment with the residents of Mujur village, where vegetable and fruit waste are collected and crushed. They are then fermented for 2 weeks with the addition of EM4 in a ratio of 1:1:100. Testing was conducted at the Mujur village farm secretariat. The results show that plants given Liquid Organic Fertilizer experienced faster stem growth. On the first day, chili plants grew 4.5 cm, and on the third day, 5.0 cm, while the comparison with ordinary water showed 4.5 cm on the first day and 8.0 cm on the second day. Based on the experimental results, it can be concluded that the treatment on the first and second day significantly proves that the liquid fertilizer produced is very good for plants.